Opting Biological and Targeted Synthetic Disease-modifying Antirheumatic drugs: Willingness to Pay, Perceptions and barriers among Pakistani Rheumatoid Arthritis Patients - Masem Afzal, Muhammad Faiq, Fahad Aman Khan, Imran Khan, Muhammad Maqsood, Umar Farooq Dar, Muhammad Arslan, Ayesha Kaleem (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Biological and targeted synthetic disease-modifying antirheumatic drugs (b/tsDMARDs) have revolutionized the treatment of rheumatoid arthritis (RA). These novel agents have costs, perceptions, barriers and misconceptions. Objective: To determine the factors associated with limited use of b/tsDMARDs among RA patients. Study design: Analytical cross-sectional study. Place and duration of study: Gulab Devi Teaching Hospital, Lahore and Gujranwala Medical College Teaching Hospital, Gujranwala from 1st January 2023 to 30th June 2023. Methodology: One hundred and sixteen patients with rheumatoid arthritis and willingness to pay to pay, perceptions regarding b/tsDMARDs and barriers rendering suboptimal use of standard treatment were included. Results: Fifty (45%) patients preferred biological and targeted synthetic disease-modifying antirheumatic drugs. Regarding perceptions and challenges, we found that patients prefer two to three tablets (56%) instead of injection-based therapy. 27% patients among sampled population perceived that injection being the last treatment should be avoided. 13% patients had needle phobia. 14% patients were willing to pay for b/tsDMARDs while 86% patients were not willing to pay because of financial constraints, Conclusion: Financial constraints are the major barrier to optimal utilization of the newer biological and targeted synthetic disease-modifying antirheumatic drugs among Pakistani patients with rheumatoid arthritis. Keywords: Conventional versus non-conventional DMARDs, Arthritis.